Simple, Low Cost, and Efficient Design of a PC-based DC Motor Drive (Journal of University of Babylon for Engineering Sciences, 2018)
In industrial applications, requiring variable speed and load characteristics, the DC motor is the attractive piece of equipment; due to its ease of controllability. Pulse-width modulation (PWM) or duty-cycle variation methods are commonly used in speed control of DC motors. A simple, low cost, and efficient design for a control circuit uses the PWM to adjust the average voltage fed the DC motor is proposed in this paper. The objective of this paper is to illustrate how the DC motor's speed could be controlled using a 555 timer. This timer works like a changeable pulse width generator. The pulse width can be changed via relays to add or remove resistors in the timer circuit. Using relays enable the proposed circuit to drive higher-power motors. The designed circuit controls the speed of a Permanent Magnet PM DC motor by means of the parallel port of a PC; therefore, the user will be able to control the speed of the DC motor. C++ computer program is used to run the motor at four levels of speed. An interface circuit is used to connect the motor to the parallel port. PC based control software is chosen to get simplicity and ease of implementation.